Permanent Wage Cost Subsidies for Older Workers. An Effective Tool for Increasing Working Time and Postponing Early Retirement? - Andrea Albanese; Bart Cockx (Center for Economic Studies and ifo Institute (CESifo), 2015)
In several OECD countries age-targeted wage subsidies have been introduced to increase the employment of older workers, but evidence on their effectiveness is scarce. This paper examines the effects of a permanent wage cost subsidy in Belgium on the employment rate, working time and hourly wage. We estimate these effects by integrating Inverse Probability Weighting in a, possibly trend-adjusted, Difference-in-Differences of endogenously sampled repeated cross sections. We find small positive short-run impacts on working time and larger ones on the employment rate, but only for employees at high risk of leaving to early retirement. The wage is not affected.
Keywords: J14; C21; J18; J30; 330; wage cost subsidies; older workers; Weighted Difference-in-Differences; endogenous sampling